Pigs lacking TMPRSS2 displayed fewer lung lesions and reduced inflammatory response when infected with influenza A virus - Ciacci Zanella, Giovana; Snyder, Celeste A.; Arruda, Bailey L.; Whitworth, Kristin; Green, Erin; Poonooru, Ravikanth Reddy; Telugu, Bhanu P.; Baker, Amy L. (Frontiers in Genome Editing, 2024)
Influenza A virus (IAV) infection is initiated by hemagglutinin (HA), a glycoprotein exposed on the virion's lipid envelope that undergoes cleavage by host cell proteases to ensure membrane fusion, entry into the host cells, and completion of the viral cycle. Transmembrane protease serine S1 member 2 (TMPRSS2) is a host transmembrane protease expressed throughout the porcine airway epithelium and is purported to play a major role in the HA cleavage process, thereby influencing viral pathogenicity and tissue tropism. Pigs are natural hosts of IAV and IAV disease causes substantial economic impact on the pork industry worldwide. Previous studies in mice demonstrated that knocking out expression of TMPRSS2 gene was safe and inhibited the spread of IAV after experimental challenge. Therefore, we hypothesized that knockout of TMPRSS2 will prevent IAV infectivity in the swine model. We investigated this hypothesis by comparing pathogenesis of an H1N1pdm09 virus challenge in wildtype (WT) control and in TMPRSS2 knockout (TMPRSS2 -/-) pigs. We demonstrated that TMPRSS2 was expressed in the respiratory tract in WT pigs with and without IAV infection. No differences in nasal viral shedding and lung lavage viral titers were observed between WT and TMPRSS2 -/-pigs. However, the TMPRSS2 -/-pig group had significantly less lung lesions and significant reductions in antiviral and proinflammatory cytokines in the lung. The virus titer results in our direct challenge model contradict prior studies in the murine animal model, but the reduced lung lesions and cytokine profile suggest a possible role for TMPRSS2 in the proinflammatory antiviral response. Further research is warranted to investigate the role of TMPRSS2 in swine IAV infection and disease.